2021
DOI: 10.3389/fctls.2021.774512
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Stability and Activity of Arginine Decarboxylase at Alkaline pH for the Production of Agmatine

Abstract: Agmatine, involved in various modulatory actions in cellular mechanisms, is produced from arginine (Arg) by decarboxylation reaction using arginine decarboxylase (ADC, EC 4.1.1.19). The major obstacle of using wild-type Escherichia coli ADC (ADCes) in agmatine production is its sharp activity loss and instability at alkaline pH. Here, to overcome this problem, a new disulfide bond was rationally introduced in the decameric interface region of the enzyme. Among the mutants generated, W16C/D43C increased both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…ADCs in E. coli, a model organism for bacterial polyamine metabolic pathways, are annotated to be either constitutive (optimal catalytic activity at pH 5.2) or inducible (optimal pH is 8.23) [30][31][32]. To characterize the enzyme activity of SP_0166, optimal pH was determined.…”
Section: Optimization Of Ph and Incubation Time To Enhance The Adc Ac...mentioning
confidence: 99%
“…ADCs in E. coli, a model organism for bacterial polyamine metabolic pathways, are annotated to be either constitutive (optimal catalytic activity at pH 5.2) or inducible (optimal pH is 8.23) [30][31][32]. To characterize the enzyme activity of SP_0166, optimal pH was determined.…”
Section: Optimization Of Ph and Incubation Time To Enhance The Adc Ac...mentioning
confidence: 99%
“…It was reported that the poly(ethylene glycol) (PEG) conjugation was used to improve the half-life in vivo, but the enzyme activity was lost upon PEG conjugation. [21] To improve RDC's stability, attempts were made to introduce a thiol bridge into the decamerforming interface, [22] but this significantly reduced catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the poly(ethylene glycol) (PEG) conjugation was used to improve the half‐life in vivo, but the enzyme activity was lost upon PEG conjugation. [ 21 ] To improve RDC's stability, attempts were made to introduce a thiol bridge into the decamer‐forming interface, [ 22 ] but this significantly reduced catalytic efficiency. With the ultimate goal of developing an anti‐cancer drug, RDC variants with enhanced enzymatic activity have advantages, such as reducing the amount of RDC required for administration, potentially leading to reduced side effects and toxicity.…”
Section: Introductionmentioning
confidence: 99%